0934 Social Rhythm Regularity Mediates The Relationship Between Depression And Nightmares In Individuals With Post-traumatic Stress Disorder And Major Depression. (27th April 2018) - Boland, E; Kelly, M; Perkins, S; Wakschal, E; Haynes, P; Gehrman, P R
Abstract: Introduction: Approximately half of individuals with PTSD are also diagnosed with major depressive disorder (MDD). Nightmares, a core feature of PTSD, are reported in patients with both current and remitted MDD. Given evidence of circadian rhythm disturbances in psychiatric disorders, there may be chronobiological influences on nightmares. The present study examined the relationship between social rhythm regularity (SRR), or consistency of daily habitual behaviors which is theoretically linked to circadian rhythms, depression, and nightmares, in a sample of individuals with comorbid PTSD and MDD. Methods: Participants were 57 male veterans who met DSM-IV-TR criteria for current PTSD and MDD. SRR was assessed via the Social Rhythm Metric. Depression severity was measured with the Hamilton Depression Rating Scale. Number of nightmares was assessed via daily sleep diary. Mediational analyses utilized Hayes' PROCESS Macro with bootstrapping assessing for direct and indirect effects. Results: Increased SRR was associated with decreased nightmares ( r = -.294, p = .03); and decreased depression severity ( r = -.285, p = .03). Depression severity was positively associated with greater number of nightmares ( r = .338, p = .006). In the mediational model, no significant direct effect of depression was found on nightmares, but SRR had a significant indirect effect on number of nightmares ( B = .0126; 95%CI: .000 - .043). Greater SRR was associated with earlier wake time on sleep diary ( r = -.420, p = .001). Conclusion: Social and possibly circadian timing may influence the occurrence of nightmares in individuals with PTSD and MDD. The finding of less SRR among those who woke later is consistent with previous reports that nightmares may be more frequent among individuals with an evening chronotype. Data support exploring the role of social rhythm stabilization in nightmare treatment. Support (If Any): Funding for this research was supported by Department of Defense #W81XWH-08-2-0121 (PI: Haynes) and American Sleep Medicine Foundation #37-CA-06 (PI: Haynes). Analysis and presentation of this research supported by: Department of Veterans Affairs IK2-CX001501 (PI: Boland) and NIH T32 HL007713-24 (PI: Pack).